2023
DOI: 10.1128/jvi.00937-23
|View full text |Cite
|
Sign up to set email alerts
|

miR-155 facilitates the synergistic replication between avian leukosis virus subgroup J and reticuloendotheliosis virus by targeting a dual pathway

Jingwen Xue,
Defang Zhou,
Jing Zhou
et al.

Abstract: Co-infection of avian leukosis virus subgroup J (ALV-J) and reticuloendotheliosis virus (REV) in poultry flocks induces synergistic replication, which worsens immunosuppression, growth inhibition, and increased mortality. However, the synergistic replication mechanism between ALV-J and REV is still not fully understood. We showed that microRNA-155 (miR-155) targets a dual pathway, PRKCI-MAPK8 and TIMP3-MMP2, which interacts with the U3 region of ALV-J and REV to promote synergistic replication between ALV-J an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Viruses may hijack the host factors for their replication and meet the requirements associated with virus replication [38,39]. For example, miR-155 facilitates the synergistic replication between ALV-J and REV by targeting the PRKCI-MAPK8 and TIMP3-MMP2 dual-pathway [40]. Thus, it is reasonable to speculate that there is a competitive relationship between ALV-J and CIAV replication during the co-infection.…”
Section: Ciav Can Efficiently Promote the Replication Ability Of Alv-jmentioning
confidence: 99%
“…Viruses may hijack the host factors for their replication and meet the requirements associated with virus replication [38,39]. For example, miR-155 facilitates the synergistic replication between ALV-J and REV by targeting the PRKCI-MAPK8 and TIMP3-MMP2 dual-pathway [40]. Thus, it is reasonable to speculate that there is a competitive relationship between ALV-J and CIAV replication during the co-infection.…”
Section: Ciav Can Efficiently Promote the Replication Ability Of Alv-jmentioning
confidence: 99%
“…After the integration of the virus genome sequence into the host genome, the viral LTR plays a key role in the activation of the cellular proto-oncogenes, a process known as promoter insertion, which ultimately leads to multiorgan hemangioma and myeloid leukosis (8). Recent studies have shown that the aberrant expression of endogenous microRNAs (miRNAs), circular RNAs (circRNAs), and long noncoding RNAs (lncRNAs) caused by ALV-J infection is closely related to avian leukosis virus-induced tumorigenesis (9)(10)(11)(12). These regulating effectors are mainly related to various activate/inactivate signaling pathways and differential expression change of genes at mRNA and protein levels.…”
Section: Introductionmentioning
confidence: 99%